Perceptions of parents on the participation of their infants in clinical research. Issue 12 (4th July 2006) - Gammelgaard, A; Knudsen, L E; Bisgaard, H
Abstract : Objective: To analyse the motivations and perceptions of parents on the participation of their infants and young children in a comprehensive and invasive clinical research study. Methods: Semistructured qualitative interviews were conducted with 23 mothers with asthma whose infants and young children were participating in the Copenhagen Prospective Study on Asthma in Childhood. The interviews were audiotaped, transcribed and analysed using the template analysis method. Results: Parents were motivated by altruism and by the opportunity to get their child checked regularly by medical experts to prevent the possible development of asthma. Parents found it very important that their children enjoyed their visits to the research clinic, and that they could withdraw from the study if their child started responding negatively to those visits. No apparent difference was seen in the attitude between the parents of children with lung or skin symptoms and those of healthy children. Conclusions: It is possible to design and accomplish invasive clinical research on infants and young children in a manner that parents find ethically sound.